Assessment for Learning Dalam Pembelajaran Menulis Karangan Narasi di Sekolah Dasar - Nulice Alerbitu; Titik Harsiati; Muakibatul Hasanah (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This study aims to describe the process of learning to write narrative essays, assessment for learning conducted by teachers, and students' ability to write narrative essays. The research method used is descriptive qualitative. The results of the research on the process of learning to write narrative essays were carried out well. Assessment for learning conducted by teachers includes the use of effective questioning methods, active feedback between teachers and students, feedback on student work, and student revision of narrative essays. The students' overall ability to write narrative essays is very good.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan proses pembelajaran menulis karangan narasi, penilaian pembelajaran yang dilakukan oleh guru, dan kemampuan menulis karangan narasi siswa kelas V SD. Metode penelitian yang digunakan adalah deskriptif kualitatif. Hasil proses pembelajaran menulis karangan narasi terlaksana dengan baik. Penilaian pembelajaran yang dilakukan oleh guru meliputi penggunaan metode tanya jawab yang efektif, umpan balik aktif antara guru dan siswa, umpan balik hasil kerja siswa, dan revisi karangan narasi siswa. Kemampuan siswa dalam menulis karangan narasi secara keseluruhan sangat baik.